2013
DOI: 10.1016/j.ypmed.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Association of the built environment with physical activity and adiposity in rural and urban youth

Abstract: Objective To determine if: (1) differences exist for body mass index (BMI) and moderate-to-vigorous physical activity (MVPA) between rural and urban youth, and (2) perceived and objective measures of environmental supports for physical activity differentially correlate with BMI and MVPA in middle school rural and urban youth. Method Cross-sectional analyses were performed in spring 2012 on data collected from December 2008 until May 2010 for 284 middle school youth from a rural county and an adjacent urbaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 20 publications
2
50
1
1
Order By: Relevance
“…In response to these findings, social cultural environmental factors such as crime, 21,68,69 safety, 70,71 social support 35,72,73 and physical environment supports for PA (e.g., sidewalks, parks, walking trails) 74 at the macro level have been considered in rural and urban settings independently, but few studies have compared across setting. 16,75,76 Access to facilities and equipment for PA is moderately associated with recreational PA and sports in urban youth 23,24,77 with few studies having confirmed these relationships in rural youth. 78-80 A review of studies examining environmental support for PA (most conducted in urban settings) determined that, as children grow, high PA was only observed in those with access to supervised PA programs and community-based sports.…”
Section: Multi-level Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to these findings, social cultural environmental factors such as crime, 21,68,69 safety, 70,71 social support 35,72,73 and physical environment supports for PA (e.g., sidewalks, parks, walking trails) 74 at the macro level have been considered in rural and urban settings independently, but few studies have compared across setting. 16,75,76 Access to facilities and equipment for PA is moderately associated with recreational PA and sports in urban youth 23,24,77 with few studies having confirmed these relationships in rural youth. 78-80 A review of studies examining environmental support for PA (most conducted in urban settings) determined that, as children grow, high PA was only observed in those with access to supervised PA programs and community-based sports.…”
Section: Multi-level Environmentsmentioning
confidence: 99%
“…78-80 A review of studies examining environmental support for PA (most conducted in urban settings) determined that, as children grow, high PA was only observed in those with access to supervised PA programs and community-based sports. 81 Similarly, access to high quality, user-friendly, supervised facilities, natural amenities, and age-appropriate programs was associated with higher levels of PA. 22,78,82,83 Unfortunately, very little research 15,75,84-87 has been conducted to compare correlates of PA among urban and rural youth.…”
Section: Multi-level Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health behavior is linked to socioeconomic and environmental aspects of where people live (Calise et al, 2013; Xu et al, 2013). Leisure-time physical activity in the United States (U.S.) is lower in rural settings (Martin et al, 2005; Michimi and Wimberly, 2010; Moore et al, 2013; Reis, et al, 2004), among minorities, women, and lower socioeconomic status individuals and communities (Cerin and Leslie, 2008; U.S. Department of Health and Human Services, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, latest research indicates that adolescents’ physical activity tends to occur close to their homes,35 42 and that strong associations exist between inactivity with lower neighbourhood walkability, amount of public open space and neighbourhood safety,43 as well as higher densities of cul-de-sac networks 36. MVPA is significantly lower for rural adolescents compared with those living in urban environments; however, these differences between neighbourhood type are not seen for body mass index (BMI) 44. Geospatial data indicate that adolescent girls engage in higher intensity physical activity in places with parks, schools and higher population density, and that they accumulate lower levels of physical activity in places with more roads and food outlets 32.…”
Section: Introductionmentioning
confidence: 99%